Cytosine N4-Methylation via M.Ssp6803II Is Involved in the Regulation of Transcription, Fine- Tuning of DNA Replication and DNA Repair in the Cyanobacterium Synechocystis sp. PCC 6803 - Gärtner, Katrin; Klähn, Stephan; Watanabe, Satoru; Mikkat, Stefan; Scholz, Ingeborg; Hess, Wolfgang R.; Hagemann, Martin (Frontiers in Microbiology, 2019)
DNA methylation plays a crucial role for gene regulation among eukaryotes, but its regulatory function is less documented in bacteria. In the cyanobacterium Synechocystis sp. PCC 6803 five DNA methyltransferases have been identified. Among them, M.Ssp6803II is responsible for the specific methylation of the first cytosine in the frequently occurring motif GGCC, leading to N4-methylcytosine (GGm4CC). The mutation of the corresponding gene sll0729 led to lowered chlorophyll/phycocyanin ratio and slower growth. Transcriptomics only showed altered expression of sll0470 and sll1526, two genes encoding hypothetical proteins. Moreover, prolonged cultivation revealed instability of the initially obtained phenotype. Colonies with normal pigmentation and wild-type-like growth regularly appeared on agar plates. These colonies represent suppressor mutants, because the sll0729 gene was still completely inactivated and the GGCC sites remained unmethylated. The suppressor strains showed smaller cell size, lowered DNA content per cell, and decreased tolerance against UV compared to wild type. Promoter assays revealed that the transcription of the sll0470 gene was still stimulated in the suppressor clones. Proteomics identified decreased levels of DNA topoisomerase 4 in suppressor cells. Collectively, these results indicate that GGm4CC methylation is involved in the regulation of gene expression, in the fine-tuning of DNA replication, and DNA repair mechanisms.